2020
DOI: 10.1136/jitc-2019-000205
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the immune signature to predict distant metastasis in patients with nasopharyngeal carcinoma

Abstract: BackgroundThe tumor immune microenvironment has clinicopathological significance in predicting prognosis and therapeutic efficacy. We aimed to develop an immune signature to predict distant metastasis in patients with nasopharyngeal carcinoma (NPC).MethodsUsing multiplexed quantitative fluorescence, we detected 17 immune biomarkers in a primary screening cohort of 54 NPC tissues presenting with/without distant metastasis following radical therapy. The LASSO (least absolute shrinkage and selection operator) log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…These results strongly suggest that the TIME has different landscapes in UECE patients. Emerging evidence demonstrates that TIME is closely associated with the prognosis of several cancers (17). In this research, we found the overall survival of three UCEC subtypes differed significantly.…”
Section: Discussionmentioning
confidence: 48%
“…These results strongly suggest that the TIME has different landscapes in UECE patients. Emerging evidence demonstrates that TIME is closely associated with the prognosis of several cancers (17). In this research, we found the overall survival of three UCEC subtypes differed significantly.…”
Section: Discussionmentioning
confidence: 48%
“…These results strongly suggest that tumor immune microenvironment has different landscapes in UECE patients. Emerging evidence demonstrates that tumor immune microenvironment is closely associated with the prognosis of several cancers 13 (Liu et al, 2020). In this research, we found the overall survival of three UCEC subtypes differed significantly.…”
Section: Discussionmentioning
confidence: 50%
“…Great effort has been made to investigate tumor immune cell infiltration and to identify immune genes of prognostic value for solid tumors (19)(20)(21). Patients with AML are able to achieve durable remission following "adoptive immunotherapy", which is also known as allogeneic stem cell transplantation (22).…”
Section: Discussionmentioning
confidence: 99%